Diseño de un área de recreación turística en el recinto Calope de Muñoz de la provincia de Cotopaxi, año 2019 - Bravo Jaña, Ángel Javier (2019)
The research was carried out with the objective of developing a design of a tourist recreation area, in the área of the FM11 farm of the Plantabal company of the Calope de Muñoz site Pangua canton, Cotopaxi province, to generate tourism development in the area, giving the inhabitants the possibility of having a recreation área and a tourist site that can generate economic income for the área. Field visits were made in order to identify the natural resources that the area possesses and implement services such as: hiking, camping, sport fishing, adventure sports (tubing), cycling and horseback riding. For the calculation of the sample size, the total population Pangua was considered with a 95% confidence level applied in the sample formula where a result was obtained from a total of 377 inhabitants were surveyed, the survey allowed to know the acceptance of the design of a tourist recreation area in the enclosure, the profile of the visitor, the services and activities that they prefer to perform in the area, which were considered to carry out the design with their respective areas taking into account the surveyed population, so that this area will be of social use in which no entrance fee will be charged and its inhabitants will be able to make use of the areas and in turn have some economic in come. For the implementation of the infrastructure would cost $ 5233.55 Keywords: Desing, recreation, developing